Torso-Like Is a Component of the Hemolymph and Regulates the Insulin Signaling Pathway in Drosophila. Issue 4 (1st April 2018) - Henstridge, Michelle A; Aulsebrook, Lucinda; Koyama, Takashi; Johnson, Travis K; Whisstock, James C; Tiganis, Tony; Mirth, Christen K; Warr, Coral G
Abstract: In Drosophila, key developmental transitions are governed by the steroid hormone ecdysone. A number of neuropeptide-activated signaling pathways control ecdysone production in response to environmental signals, including the insulin signaling pathway, which regulates ecdysone production in response to nutrition. Here, we find that the Membrane Attack Complex/Perforin-like protein Torso-like, best characterized for its role in activating the Torso receptor tyrosine kinase in early embryo patterning, also regulates the insulin signaling pathway in Drosophila . We previously reported that the small body size and developmental delay phenotypes of torso-like null mutants resemble those observed when insulin signaling is reduced. Here we report that, in addition to growth defects, torso-like mutants also display metabolic and nutritional plasticity phenotypes characteristic of mutants with impaired insulin signaling. We further find that in the absence of torso-like, the expression of insulin-like peptides is increased, as is their accumulation in insulin-producing cells. Finally, we show that Torso-like is a component of the hemolymph and that it is required in the prothoracic gland to control developmental timing and body size. Taken together, our data suggest that the secretion of Torso-like from the prothoracic gland influences the activity of insulin signaling throughout the body in Drosophila .